Pet ownership in childhood and socio-emotional characteristics, work values and professional choices in early adulthood - Vizek-Vidović, Vlasta (Array, 2001)
The main goal of this study, partly retrospective in character, was to explore if and how pet ownership in childhood is related to several indicators of socio-emotional development, as well as work values and professional choices in early adulthood. The sample consisted of 356 students (200 females, 156 males) from different colleges of the University of Zagreb, representing helping (n=200) and non-helping (n=156) professions. The mean age of the students was 21 years. Seventy-four percent of the participants had had a pet during childhood, mostly dogs. Participants who had owned a pet during childhood reported quite a strong attachment to it. In addition, pets were rated lower than family members and friends, but higher than television, relatives and neighbors in terms of the social support derived from them during childhood. Discriminant analysis was performed in order to examine whether young adults - those who had owned a pet during childhood and those who hadn't - differed in emotional and motivational characteristics, and whether there was a correlation with their chosen subject of study. Pet ownership in childhood was a grouping Variable, while measures of current socio-emotional functioning (empathy, prosocial behavior, social anxiety and loneliness), value orientations (self-actualisation, individualistic, social, utilitarian and adventurous) and chosen subject of study (helping or non-helping profession) were predictors. A significant discriminant function was obtained. Correlations between discriminating variables and discriminant function showed that young adults who had had a pet during childhood were more empathetic, more prone to choose helping professions, and more oriented towards social values than those who did not have a pet during childhood.